Determinants Quality of Life For Chronic Kidney Disease Patients Undergoing Hemodialysis Therapy - Nurarifah; Gustini; Sukmawati; Mua, Estelle Lilian; Ra’bung, Alfrida Semuel (YCAB Publisher, 2025)
Background:Hemodialysis is a kidney replacement therapy for patients with chronic kidney disease (CKD) aimed at removing excess fluid and waste products from the bloodstream and extending life expectancy. Although hemodialysis is considered the most effective therapy for increasing the life expectancy of CKD patients, it is associated with several side effects that can impact patients' overall well-being. Objective:This study aims to analyze the quality of life and associated factors among chronic kidney disease patients undergoing hemodialysis therapy. Methods:This cross-sectional study was conducted in the Hemodialysis Unit of Banggai District Hospital, Central Sulawesi, Indonesia. The study involved 60 CKD patients aged ≥18 years who were undergoing hemodialysis therapy from April to June 2024. Participants were selected using purposive sampling. Primary data were collected through direct interviews using the Kidney Disease Quality of Life Short Form 36 (KDQoL-SF36) questionnaire. Data analysis was performed using descriptive statistics, chi-square tests, and logistic regression analysis. Results:The chi-square test revealed significant associations between age (p = 0.024), gender (p = 0.041), blood pressure (p = 0.036), nutritional status (p = 0.039), hemoglobin levels (p = 0.024), creatinine levels (p = 0.023), and family support (p = 0.003) with the overall quality of life of hemodialysis patients. Logistic regression analysis demonstrated that gender (p = 0.025; OR = 8.739; 95% CI: 1.320–57.872) and blood pressure (p = 0.049; OR = 9.817; 95% CI: 1.012–95.251) were significant predictors of quality of life. Conclusion:Factors such as older age, female gender, hypertension, nutritional imbalances (obesity or malnutrition), anemia, and elevated creatinine levels contribute to a decline in the quality of life of hemodialysis patients. The findings underscore the importance of collaborative efforts by patients, families, nurses, healthcare providers, and the government to enhance therapy adherence, dietary management, and psychological support to improve the quality of life of patients undergoing hemodialysis. Keywords:quality of life; chronic kidney disease; hemodialysis; hemoglobin; creatinine